Population biology of Callinectes ornatus Ordway, 1863 (Decapoda, Portunidae) from Ubatuba (SP), Brazil - Negreiros-Fransozo, M. L. [UNESP]; Mantelatto, F. L. M.; Fransozo, A. [UNESP] (Editorial CSIC, 1999)
Population structure and reproductive season of the portunid crab Callinectes ornatus were studied in animals collected from the Ubatuba bays, Sao Paulo, Brazil (23°20' to 23°35' S and 44°50' to 45°14' W). The samples were taken in three trawls performed every other month from January 1991 to May 1993. A total of 3,829 specimens of C. ornatus were obtained. Their size ranged from 9.3 to 84.6 mm (carapace width). Their median size based on their cephalothoracic width and their size frequency were determined as well. Their reproduction was continuous, with variable proportions of ovigerous females. The highest incidence of ovigerous females occurred in January 1991, 1992 and 1993 and March and November 1992. The oscillations of the environmental factors between the seasons are not so intense in subtropical regions, therefore allowing the continuity of the physiological process of growth and reproduction throughout the year.
Keywords: Callinectes; Portunidae; Reproduction; South Brazilian coast; crustacean; population structure; reproductive biology; Brazil; Animalia; Callinectes ornatus; Crustacea; Decapoda (Crustacea)